Combined PCR and Q-RT-PCR technique for detecting chimerism in a non-human Primate vascularized osteomyocutaneous allografts model - Jiang, J; Wang, J; Zhong, F; Chen, G; Li, Y; Zheng, X X (Cellular and Molecular Biology, 2016)
Face transplantation and other composite tissue transplantation (CTA) are permissive to transplantation tolerance. The real reason, that composite tissue containing bone achieves transplantation immune tolerance more easily than the composite tissue without the bone is not clear. The chimerism may be the main mechanism in the progress of inducing the transplantation tolerance by CTA. We currently have established a non-human Primate Vascularized Osteomyocutaneous Allografts Model. To test the chimerism which comes from donor after the transplantation, we developed a method which combined reverse transcription polymerase chain reaction (RT-PCR) and real-time quantitative PCR (qRT-PCR) technique using primers specific for Macaca fascicularis sex determination region on the Y chromosome (SRY) gene. With the method, we estimated the level of the chimerism.